Africa Business Research as a Laboratory for Theory-Building: Extreme Conditions, New Phenomena, and Alternative Paradigms of Social Relationships. (5th October 2017) - Barnard, Helena; Cuervo-Cazurra, Alvaro; Manning, Stephan
ABSTRACT: Africa is an increasingly important business context, yet we still know little about it. We review the challenges and opportunities that firms in Africa face and propose that these can serve as the basis for extending current theories and models of the firm. We do so by challenging some of the implicit assumptions and stereotypes on firms in Africa and by proposing three avenues for extending theories. One is taking the extreme conditions of some Africa countries and using them as a laboratory for modifying current theories and models of the firm, as we illustrate in the case of institutional theory and the resource-based view. A second one is identifying new themes that arise from analyzing firms in Africa and their contexts of operation, and we discuss four themes: migrating multinationals and the meaning of home country, diaspora networks within and across countries, a recasting of cultural and institutional distance, and new hybrid organizational forms. A third one is developing new theories based on alternative paradigms of social relationships that have emerged in Africa that differ from those underpinning existing theories of the firm, such as kgotla and its view of community-based relationships or ubuntu and its humanizing view of relationships.